Standardization and characterization of Mohanthal using response surface methodology - M. B. Chaudhary; K. Jayaraj Rao; Ankit Bihola; Shaikh Adil (Scientific Reports)
Abstract Mohanthal, a traditional Indian sweet made from chickpea flour, ghee, khoa, and sugar, holds significant cultural and culinary importance. However, its preparation lacks standardization, resulting in inconsistencies in quality that hinder large-scale production and commercialization. This study addresses these challenges by employing Response Surface Methodology with a Central Composite Design to optimize the ingredient formulation of Mohanthal, ensuring consistent quality while preserving its traditional essence. Experiments were conducted to evaluate the effects of varying levels of ghee, khoa, and sugar on sensory, textural, and color attributes, with chickpea flour kept constant. The optimized formulation, comprising 103.13 g of ghee, 27.70 g of khoa, 98.24 g of sugar, and 100 g of chickpea flour, exhibited superior sensory and textural characteristics, including enhanced flavor, color, and consistency. Quadratic models developed for key attributes, such as sensory scores, textural parameters, and browning index, demonstrated excellent predictive capabilities with R2 values exceeding 0.90, confirming the robustness of the optimization approach. This study significantly contributes to the scientific understanding of Mohanthal production by providing a validated and standardized formulation. The findings bridge the gap between traditional preparation methods and modern food technology, enabling consistent quality control and scalability for commercial production. By addressing the challenges of variability and preserving the cultural essence of this traditional sweet, this work lays a foundation for its large-scale manufacturing and market potential.